The relationship between the internal communication and employees' commitment to change in the large companies in Malaysia - Marchalina, Leonis; Ahmad, Hartini (2017)
Internal communication is very significant to communicate change effectively in the large companies and support the employees’ commitment to change as reported in this current study. Therefore, the study intends to fill the gaps in the relationship between Internal Communication and Employees’ Commitment to Change.The research framework is a hypothetical deduction based on the Lewin’s Three Step Model, which came out from the literature review that the Internal Communication influences the Employees’ Commitment to Change. The study embarked on the quantitative survey that was sent out to the employees from the Malaysian large companies and the various sectors.The study used a stratified and simple random sampling to ensure the representatives from each identified clusters.The key findings showed that the clear information and leaders’ effort to communicate change to their employees related heavily on the Employees’ Commitment to Change.This study meets the objectives that successfully discovered that the Internal Communication influence the employees’ commitment to change, and hope it could contribute to the body of knowledge, particularly contributed to the Strategic Management field. In terms of the practical implication, this study could assist both top management and employees to appreciate the environment for the commitment to change in order to meet the desirable results.